Infectious complications during the initial 225 cases of standard PCNL: A single center experience - Karki, Kushal; Bhusal, Narayan (Journal of Society of Surgeons of Nepal, 2021)
Introduction: Percutaneous nephrolithotomy(PCNL) has emerged as the treatment of choice for medium to large urinary stones. Infection is a life threatening complication and is the most common cause of death following PCNL. This study aimed to examine different predictors of infective complications in PCNL. Methods: This retrospective study was done on patients who underwent PCNL between 2016 and 2020 at a tertiary level medical college hospital. Medical records were reviewed for study variables. Results: Two hundred and twenty five cases were included out of which 121 were male. A total of 151 complications were recorded among which 27(17.88%) were major complications. Infectious complications were seen in 67 (29.77%) patients among which 39 cases (17.33%) were febrile urinary tract infections. Urosepsis developed in four patients and one patient died due to urosepsis related complication. Female (p=0.003), Diabetes mellitus (p=0.002), positive urine culture (p=0.0001), stone location (p=0.01), degree of hydronephrosis (p=0.001), duration of surgery (p=0.001), number of access tracts (p=0.0001), and initial 100 cases (p=0.001) were associated with post PCNL infections. Conclusion: Female, Diabetes mellitus, preoperative urine culture positivity, stone location, degree of hydronephrosis, duration of the operation, number of access tracts and surgeon experience are risk factors for post PCNL infections. Surgeons should be extra vigilant during their initial period. Urinary tract infection should be treated and extra care should be taken when operating in female patients giving ample attention to preoperative investigations.